Real-world observational study on the long-term effect of L-glutamine treatment on renal parameters of adult and pediatric patients with sickle cell disease - Elenga, Narcisse; Yassin, Mohamed A. (Frontiers in Medicine, 2023)
Background Sickle cell disease (SCD) is a rare genetic blood condition affecting millions worldwide. Oxidative stress is a key player in the pathogenesis of SCD and its comorbid consequences. Renal function impairment is a common complication of SCD in both pediatric and adult patients with serious consequences leading to increased risk of mortality. In this observational real-world study, we are reporting the long-term (120 weeks) renal function in 10 patients treated with L-glutamine. Methods Ten patients (4 pediatric and 6 adults), with confirmed diagnoses of SCD (HbSS genotype), were enrolled, these included four patients from Qatar with Arab Indian haplotype and six patients from French Guiana with African haplotype. All patients were treated with L-glutamine oral powder (~0.3 g/kg body weight, Endari®) twice daily for 120 weeks. Clinical events and laboratory parameters (renal function, hemoglobin, reticulocytes, and lactate dehydrogenase [LDH]) were measured at baseline, 48, and 120 weeks. Results The study showed that with L-glutamine treatment there were improvements in renal and hematological parameters with no vaso-occlusive crisis at both 48-and 120-week follow-up time points in all 10 patients. Improvements were seen in the albumin creatinine ratio (ACR) from baseline to 48 weeks (mean [Standard deviation SD] ACR: −4.19 [9.81] mg/g) and 120 weeks (mean [SD] ACR: −12.31 [21.09] mg/g). Mean (SD) increase in hemoglobin concentrations from baseline to 48 weeks and 120 weeks was 0.72 (1) g/dL and 1.41 (0.79) g/dL, respectively. Mean (SD) reticulocyte counts and LDH levels decreased from baseline to 48 weeks (mean [SD] change from baseline to 48 weeks, reticulocyte counts: −40.30 [101.58] × 109 cells/L; LDH levels: −259 [154.93] U/L) and 120 weeks (mean [SD] change from baseline to 120 weeks, reticulocyte counts: −58.30 [128.38] × 109 cells/L; LDH levels: −344.80 [274.63] U/L). Conclusion This is one of the first studies that assessed the long-term renal outcomes in SCD using L-glutamine. L-glutamine improved the renal function in patients with SCD along with improvements in clinical outcomes and hemolysis, from 48 weeks and sustained through 120 weeks of treatment.